P261 Severe neutropenia and mssa lymphadenitis after influenza-b infection. (6th June 2017) - Erat, Tuğba; Yahši, Aysun; Kara, Tuğçe Tural; Süzen, Eda; Özdemir, Halil; Ertem, Mehmet; Çiftçi, Ergin; Ince, Erdal
Abstract : A two year old patient presented with high fever, weakness was prescribed antibiotics on an outpatient basis, but her fever persisted for ten days. She was admitted to the Infectious Diseases Unit with the diagnosis of lymphadenitis. On arrival, the patient's left submandibular lymp node was 4cmx4cm, right submandibular lymph node was 4cmx3cm, both hard and tender by palpation. Cervical ultrasound was performed, and the lymph nodes were primarily considered as lymphadenitis. Intravenous Ampicillin-Sulbactam and Clindamycin treatment was started. When the patient's previous laboratory analyses were examined, it was seen that she 600 neutrophils were counted. Latest peripheral blood smear eighty six neutrophils were counted. The patient was consulted to the Paediatric Haematology Department. In order to determine the cause of her long-term neutropenia, blood marrow aspiration was performed and malignancy was ruled out. G-CSF treatment was advised. EBV, CMV and HSV serology tests were resulted negative. The patient's blood, urine, faeces cultures also resulted negative. The preliminary diagnosis was primer immun neutropenia of infancy. Influenza B was reported in her respiratory viral PCR, oseltamivir was added to her treatment. After G-CSF treatment, the patient's neutrophil count was rised and Lymphadenpathy was softened. Lymph node dreinage was performed from the left sumbandibular lymph node. The culture sent from the dreinage resulted as S. aureus positive. On the fourth week of the antibiotic treatment, lymph nodes were not palpable and acute phase reactants had decreased. After influenza B infection neutropenia can deepen and increased risk for bacterial infections such as Lymphadenitis